PENJINAKAN DAN BUDIDAYA IKAN BREK (Puntius orphoides) SEBAGAI UPAYA MENUJU DIVERSIFIKASI USAHATANI IKAN DOMESTICATION AND CULTURE OF TINFOIL BARB (Puntius orphoides) AS AN EFFORT TOWARD FISH FARMING DIVERSIFICATION - Setyaningrum, Nuning; Nuryanto, Agus (Pembangunan Pedesaan, 2006)
Aims of this research were to investigate hatching rate of Puntius orphoides eggs resulted from artificial spawning and the effect of different water inlet number with different water debit and food on growth rate and survival rate of P. orphoides fry. Experimental method with factorial pattern was used. The first factor was ponds culture without water inlet and with one water inlet (10 LPM/m³ water debit), two water inlets (20 LPM/m³ water debit), and three water inlets (30 LPM/m³ water debit). The second factor was feeding with pellet and Tubifex. Each treatment was repeated twice. Parameter measured was number of hatched egg, increasing of body weight, length and survival rate. The data was analyzed by one way anova and further analysis with Duncan test. Result showed that P. orphoides could spawn in culture ponds with hatching rate of the egg was 82%. The highest growth rate was reached in the ponds with three water inlets (30 LPM/m³ water debit), while the best survival rate was reached in culture ponds with three water inlets (30 LPM/m³ water debit). Pellet food and Tubifex gave the same effect on the fish growth.